Expression of HER2 and Mismatch Repair Proteins in Surgically Resected Gallbladder Adenocarcinoma - Sung, You-Na; Kim, Sung Joo; Jun, Sun-Young; Yoo, Changhoon; Kim, Kyu-Pyo; Lee, Jae Hoon; Hwang, Dae Wook; Hwang, Shin; Lee, Sang Soo; Hong, Seung-Mo (Frontiers in Oncology, 2021)
Background: Gallbladder cancer (GBC) has a poor prognosis. Although complete surgical resection is the only successful approach for improving survival, additional therapeutic modalities are required for recurrent or surgically unresectable GBCs. Materials and Methods: To determine the expression status of HER2 and the mismatch repair (MMR) proteins MLH1, MSH2, MSH6, and PMS2, immunohistochemical staining of MMR proteins and HER2 was carried out in 216 surgically resected GBCs. HER2 labelling was scored by adopting a scoring system for gastric carcinomas. Tissues scoring 0 to 2+ were defined as HER2 negative, while those scoring 3+ were regarded as HER2 positive. Additionally, silver in situ hybridization and microsatellite instability (MSI) analysis were conducted to confirm HER2 amplification and MSI, respectively. Results: Three out of 216 GBCs (1.3%) showed MMR protein deficiency. All three observed MSI cases exhibited dual loss of MSH2 and MSH6 protein expression. However, no cases showed loss of either MLH1 or PMS2 expression. No association was observed between MMR protein deficiency and other clinicopathological factors. HER2 amplification was noted in 30 (13.9%) GBCs and associated with Crohn’s-like lymphoid reaction (P = 0.023). No survival difference was observed based on HER2 overexpression or HER2 amplification status. Conclusion: MMR protein deficiency and HER2 overexpression were observed in a small subset (1.3% and 13.9%, respectively) of GBCs, in a mutually exclusive pattern. The presence of Crohn’s-like lymphoid reaction may help identify cases with HER2 amplification, by using hematoxylin-stained slides. Although the proportion of MMR protein-deficient- and HER2-overexpressing GBCs was small, applying immunotherapy to MMR protein-deficient GBCs and Herceptin to HER2-overexpressing GBCs may provide alternative treatment options for patients with GBC.